Neutrino energy and momentum emission from magnetized dense quark matter - Ritesh Ghosh; Igor A. Shovkovy (Journal of High Energy Physics)
Abstract Using first-principles field-theoretic methods, we investigate neutrino emission from strongly magnetized dense quark matter under conditions relevant to compact stars. We develop a customized approximation that fully accounts for the Landau-level quantization of electron states while neglecting such quantization for quarks. This approach is well-justified in dense quark matter, where the chemical potentials of up and down quarks significantly exceed those of electrons. Our analysis provides a detailed exploration of the influence of strong magnetic fields on neutrino emission, including both the modification of the total emission rate and the emergence of emission asymmetry relative to the magnetic field direction. We further examine the role of temperature in smoothing the oscillatory behavior of neutrino emission as a function of magnetic field strength. Additionally, we study the interplay between the Landau-level quantization of electrons and the Fermi-liquid effects of quarks in modifying the phase space of relevant weak processes. Finally, we briefly discuss the broader implications of magnetic fields on stellar cooling processes and the potential contribution of asymmetric neutrino emission to pulsar kicks.